2009
DOI: 10.1007/s11606-009-1013-x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Prescribing of Heavily Marketed Medications: A Randomized Controlled Trial

Abstract: clinicaltrials.gov Identifier: NCT00788346.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…As presented in Additional file 2, Table S2, the majority of CCDSS systems in our sample were integrated with an EMR (n = 38/61, 62%) [17,18,20,23-26,28,31,32,34,40,42,44-47,49,55,56,58-66,68-70,73,74,77-85,87,89], delivered feedback via a computer display (n = 44/62, 71%) [17,18,20,23-26,28,30-36,38-40,42,44,46-49,51,55-58,60-66,68-71,73-76,80,82-84] at the time of care (n = 53/64, 83%) [16-21,23-26,28,30-35,38,40,42,44,46-51,53,55-58,60-70,72-85,87-89]. A minority of authors reported testing a CCDSS with a graphical user interface (n = 22/25, 88%) [16-18,20,21,23-25,28,30,31,34,38,40,45,46,55,56,58-60,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As presented in Additional file 2, Table S2, the majority of CCDSS systems in our sample were integrated with an EMR (n = 38/61, 62%) [17,18,20,23-26,28,31,32,34,40,42,44-47,49,55,56,58-66,68-70,73,74,77-85,87,89], delivered feedback via a computer display (n = 44/62, 71%) [17,18,20,23-26,28,30-36,38-40,42,44,46-49,51,55-58,60-66,68-71,73-76,80,82-84] at the time of care (n = 53/64, 83%) [16-21,23-26,28,30-35,38,40,42,44,46-51,53,55-58,60-70,72-85,87-89]. A minority of authors reported testing a CCDSS with a graphical user interface (n = 22/25, 88%) [16-18,20,21,23-25,28,30,31,34,38,40,45,46,55,56,58-60,…”
Section: Resultsmentioning
confidence: 99%
“…A minority of authors reported testing a CCDSS with a graphical user interface (n = 22/25, 88%) [16-18,20,21,23-25,28,30,31,34,38,40,45,46,55,56,58-60,63,65,70,73,75,83], pilot-testing the system before the trial (n = 25/45, 56%) [17-19,24,28,29,31-33,35,38,39,43-45,47,48,55,59,63,66,70-72,74,75,77-79,84], or training users on system use (n = 29/52, 56%) [16,19,21,26,28,29,31,32,34,35,38,43-47,53,56-60,62,64-66,69,75-79,83-85]. Data required by the CCDSS to produce recommendations were most commonly entered via EMR link (n = 32/61, 52%) [17,18,20,24,26,28,31,32,34,40,44-47,49,51,55,56,58-60,62-66,68-…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many published studies on prescribing alerts. These include reports of alert's effectiveness in reducing inappropriate medications for elderly patients in the emergency department and other settings,[ 11 12 13 ] reducing prescribing of heavily marketed hypnotic medications in ambulatory care settings,[ 14 ] and reducing overall prescribing of antimicrobials in addition to improving the appropriateness of antimicrobial prescribing. [ 15 16 17 ] According to a review of the literature on prescribing alerts in the elderly, a wide variety of CPOE interventions show clear potential to reduce inappropriate prescribing and polypharmacy in this population, but none of these have yet been widely adopted.…”
Section: Discussionmentioning
confidence: 99%